Studi Deskriptif Motivasi Intrinsik Siswa Dalam Mengikuti Ekstrakurikuler Tata Boga di SMA Negeri 8 Surabaya (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to describe the level of students’ intrinsic motivation in participating in the Culinary Extracurricular Program at SMA Negeri 8 Surabaya and to analyze the forms of their internal drive. The research method used is descriptive quantitative. The subjects of this study were 65 tenth and eleventh-grade students who participated in the Culinary Extracurricular Program. The research instrument was a Likert scale questionnaire (1–4) consisting of 18 items based on Self-Determination Theory (SDT), covering three indicators: autonomy, competence, and relatedness. The results showed that 87.69% of students had a high level of intrinsic motivation, 12.31% were in the moderate category, and none were in the low category. Among the three indicators, competence was the most dominant internal drive (34.0%), followed by relatedness (33.3%) and autonomy (32.7%). This high level of intrinsic motivation indicates that students are internally driven to actively participate in the Culinary Extracurricular Program.